The Effect Of Returnon Asset Returnon Equity And Current Ratio On Company Value With Good Corporate Governance As Moderating Variables : Pengaruh ROA, ROE , CR Terhadap Nilai Perusahaan dengan Good Corporate Governance sebagai Variabel Moderasi - Yolanda Nova; Enny Maryanti (Universitas Muhammadiyah Sidoarjo, 2021)
This study uses a quantitative approach. Sampling is ii purposive sampling. the initial population of 81 companies after passing the criteria stage, the remaining 51 companies were used in this study. The data analysis technique used is the Outer Model to test the validity and reliability of the data and the Inner Model to test the hypothesis using the SmartPLS version 3.0 program. The results of this study indicate that: 1) Good Corporate Governance cannot moderate the relationship between4redcx ROA and firm values ​​as evidenced by a p-value of 0.52 and a t-statistic value of 1.944, 2) Good Corporate Governance does not can moderate the relationship between ROE and firm value as evidenced by a p-value of 0.120 and a t-statistic value of 1.556, 3) Good Corporate Governance cannot moderate the relationship between CR and firm values ​​as evidenced by a p-value of 0.314 and the t-statistic value is 1.009.